IMPORTANCE OF LABORATORY STUDIES IN THE FORMATION OF STUDENTS’ RESEARCH SKILLS - Karpets, M. (World of Medicine and Biology, 2015)
The article reveals the role of laboratory work on discipline "Medical Chemistry" for the first-year students’ research work, characterized by the ability to transform acquired practical skills in the highly professional skills. The basic directions of research work are presented by the "Center of bioelementology, as part of the Department.
Keywords: laboratory classes; research work; professional training